Physicochemical Stability of Mozobil® (Plerixafor) Solution for Injection in Glass Vials and Plastic Syringes over a Three-Month Storage Period - Kim Sun Hee; Thiesen Judith; Krämer Irene (De Gruyter, 2016)
Background: The stability of ready-to-administer parenteral preparations is an important issue of drug safety. Profound knowledge about the physicochemical stability is necessary in order to determine the "beyond-use-dates" of solutions in injection vials after first opening and ready-to-administer preparations in syringes.